224k views
19 votes
How would you solve for the question below???
step by step please and thanks.

How would you solve for the question below??? step by step please and thanks.-example-1

2 Answers

0 votes

Answer:x = 4 y = 3

Explanation:

User David Millar
by
5.2k points
11 votes

Combine the two equations in the right amounts to eliminate y :

-2 (2x + 3y) + (3x + 6y) = -2 (17) + 30

-4x - 6y + 3x + 6y = -34 + 30

-x = -4

x = 4

Solve for y :

2x + 3y = 17

8 + 3y = 17

3y = 9

y = 3

User Ramanpreet Singh
by
5.7k points